2015
DOI: 10.1016/j.ijid.2015.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Viruses and Gram-negative bacilli dominate the etiology of community-acquired pneumonia in Indonesia, a cohort study

Abstract: Viruses and Gram-negative bacilli are dominant causes of CAP in this region, more so than S. pneumoniae. Most of the bacteria have wild type susceptibility to antimicrobial agents. Patients with severe disease and those with unknown etiology have a higher mortality risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
1
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 22 publications
4
20
1
3
Order By: Relevance
“…We found that obesity and need for invasive mechanical ventilation were the only two risk factors associated with increased incidence of viral CAP; however, obesity was the only independent risk factor associated with influenza CAP. This is consistent with findings of animal models which suggested a role of leptin dysregulation in more severe disease [33,34], while a higher incidence and severity of viral CAP was found in obese patients [30,31,35,36]; on the other hand, several studies showed that severity of CAP and need for ICU admittance with invasive ventilation were not associated with etiology [10,17,21,[37][38][39]. Thus, we conclude that obesity is the only independent risk factor predisposing patients to influenza infection, although the association of obesity and viral CAP, and then, with influenza CAP, could be over-represented by the large proportion of patients with Influenza virus diagnosed in this cohort.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We found that obesity and need for invasive mechanical ventilation were the only two risk factors associated with increased incidence of viral CAP; however, obesity was the only independent risk factor associated with influenza CAP. This is consistent with findings of animal models which suggested a role of leptin dysregulation in more severe disease [33,34], while a higher incidence and severity of viral CAP was found in obese patients [30,31,35,36]; on the other hand, several studies showed that severity of CAP and need for ICU admittance with invasive ventilation were not associated with etiology [10,17,21,[37][38][39]. Thus, we conclude that obesity is the only independent risk factor predisposing patients to influenza infection, although the association of obesity and viral CAP, and then, with influenza CAP, could be over-represented by the large proportion of patients with Influenza virus diagnosed in this cohort.…”
Section: Discussionsupporting
confidence: 89%
“…However, early diagnosis and treatment of viral CAP caused by Influenza virus is known to have notable clinical implications [20]. In this regard, several studies showed that prevalence of viral CAP varies from 15% to 35% [2,7,9,10,21-23]; however, these studies limit data analyses to only tested patients or all the patients enrolled were systematically tested for viral infection [2,7,9,10,[21][22][23]. In the present study, which was an attempt to assess real-life scenarios, < 15% of patients were tested for viruses with a prevalence of viral CAP of 28.4% among those tested, consistent with the recent results of a systematic review [7].…”
Section: Discussionmentioning
confidence: 99%
“…Gram negative bacteria predominated the organisms in this study, similar to the results of H. Farida et al [26]. Detection of mycobacterium tuberculosis was observed to be high.…”
Section: Discussionsupporting
confidence: 91%
“…In South Africa and some Asian countries, Klebsiella pneumoniae is a common cause of severe bacteraemic CAP, displacing S . pneumoniae as the most common bacterial cause in some cohorts . Acinetobacter baumannii —typically associated with nosocomial pneumonia in high‐income countries—has also been identified as a cause of severe CAP in tropical settings .…”
Section: Pneumonia Aetiologymentioning
confidence: 99%
“…The utility and cost‐effectiveness of different diagnostic modalities will also vary by region and context. Whilst blood cultures are an expensive and usually fairly insensitive diagnostic modality in CAP, in a Southeast Asian setting, for example, with high rates of bacteraemic Gram‐negative disease, the facility might be valuable . Diagnostic tests for use in community‐level facilities must require minimal staff training and laboratory infrastructure to perform .…”
Section: Diagnosis and Assessmentmentioning
confidence: 99%